2016
DOI: 10.1155/2016/3267307
|View full text |Cite
|
Sign up to set email alerts
|

Interspinous Process Decompression: Expanding Treatment Options for Lumbar Spinal Stenosis

Abstract: Interspinous process decompression is a minimally invasive implantation procedure employing a stand-alone interspinous spacer that functions as an extension blocker to prevent compression of neural elements without direct surgical removal of tissue adjacent to the nerves. The Superion® spacer is the only FDA approved stand-alone device available in the US. It is also the only spacer approved by the CMS to be implanted in an ambulatory surgery center. We computed the within-group effect sizes from the Superion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…In this study, only 9% of the patients had to be reoperated during the FU period, because of complications or lack of effectiveness. Similar results have been reported by Surace et al (12), describing an improvement in Oswestry Disability Index (ODI) and ZCQ scores over an 18-month FU period, and by Nunley et al (13) and by Patel et al over a 3-year FU period (14).…”
Section: Discussionsupporting
confidence: 83%
“…In this study, only 9% of the patients had to be reoperated during the FU period, because of complications or lack of effectiveness. Similar results have been reported by Surace et al (12), describing an improvement in Oswestry Disability Index (ODI) and ZCQ scores over an 18-month FU period, and by Nunley et al (13) and by Patel et al over a 3-year FU period (14).…”
Section: Discussionsupporting
confidence: 83%
“…Biomechanical study (94) showed the interspinous spacer significantly increased the canal area by 18%, subarticular diameter by 50%, canal diameter by 10%, the foraminal area by 25%, and the foraminal width by 41% in extension. Therefore, interspinous spacer is an alternative choice for LSS nowadays (95), it can be inserted percutaneously alone without decompression or combined with open or microsurgical decompression. The percutaneous standalone spacer implantation has advantages of being minimally invasive (96,97), however, may have high risk of unsatisfactory back pain, leg pain, quality of life and failure of implantation (98).…”
Section: Interspinous Spacermentioning
confidence: 99%
“…There is a growing body of published literature to support the safety and effectiveness of interspinous process decompression (IPD) with stand-alone interspinous spacers in the treatment of moderate LSS. 22 , 23 Spacers provide immediate symptom amelioration by serving as a spinal extension blocker to prevent the repetitive compression of neurovascular elements during back extension that is the primary source of LSS symptoms. Clinical follow-up from a US Food and Drug Administration (FDA) investigational device exemption (IDE) randomized controlled trial of the Superion device extends to 5 years of published findings.…”
Section: Introductionmentioning
confidence: 99%